Conferences, community, and technology: Avoiding a crisis - Grudin, Jonathan (Proc. iConference 2010., 2010)
Computer Science in North America has embarked on a course unique in academic scholarship. It has turned conferences into repositories of polished work, little of which ever evolves into journal articles. Senior researchers feel that the conferences are in crisis. I consider the origins and consequences of the shift to conferences, concluding that it has led to an evolutionary cul-de-sac that the Information field would do well to avoid. The crisis is described as centered on reviewing, but it is at heart a crisis of community.
http://hdl.handle.net/2142/14921